A Comparative of Deixis Found in the Speech of Mike Pompeo and Retno Marsudi - Aisyah Nurul Afiefah; Dedi Sofyan; Ira Maisarah (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
In listening to speeches sometimes there is a misunderstanding in interpreting the meaning of the speech in question. Through deixis can help listeners to understand the intended meaning of utterances in speech. Therefore, the purpose of this study was to describe the types of deixis in speeches delivered by Mike Pompeo and Retno Marsudi. This study used a qualitative method using descriptive analysis as a data analysis technique. Data collection techniques used documentation techniques sourced from speeches by Mike Pompeo and Retno Marsudi. The research data was collected from 6 speeches sourced from 3 speeches delivered by Mike Pompeo and 3 speeches delivered by Retno Marsudi. The data analysis technique is by identifying and interpreting all types of deixis in speeches, classifying the types of deixis found in ministerial speeches, and making conclusions. The results show that there are five types of deixis found in Mike Pompeo speech, namely: people deixis, time deixis, place deixis, social deixis, and discourse deixis. Meanwhile, in Retno Marsudi speech, only 4 types of deixis were found, namely; people deixis, time deixis, social deixis, and discourse deixis. Differences are shown in the use of place deixis. The most dominant deixis used is person deixis in both speeches. Thus, the dominant type of deixis in speech can reflect the relationship between language structure and context that is not separated and must be communicated contextually and pragmatically. When listening to a speech, listeners can identify several types of deixis and make it easier for listeners to know the types of deixis in the speech.